Опасная приманка: роман / Н. В. Степанов - Степанов Николай Викторович (Фантастический боевик, 2012)
Экземпляры: 6 () / Инвентарный номер: 50399 / Цена: 64.00 / Авт.знак: С 79 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44